A One‐Way Mirror: High‐Performance Terahertz Optical Isolator Based on Magnetoplasmonics. Issue 19 (8th July 2018) - Lin, Shuai; Silva, Sinhara; Zhou, Jiangfeng; Talbayev, Diyar
Abstract: The magneto‐optical properties of conduction electrons in InSb in Voigt geometry at oblique incidence angles are explored. In parallel magnetic field, the oblique incidence reflectance exhibits high nonreciprocity, while the transmittance remains reciprocal. This phenomenology, combined with the unique magnetoplasmonic properties of InSb (high electron mobility, low effective mass, and temperature‐tunable bulk plasma frequency), allows the design of a simple and high‐performance THz optical isolator that works directly with linearly polarized light. It is demonstrated that the isolation power of the device exceeds 35 dB with the insertion loss of only −6.2 dB. The simplicity of the isolator design is unmatched among the proposed THz isolator concepts to date. Abstract : A high‐performance terahertz isolator based on the nonreciprocal reflectance of conduction electrons in magnetic field is experimentally demonstrated. The unique properties of InSb, such as a low electron scattering rate and a low electron effective mass, allow the isolator operation at room temperature and moderate magnetic field as low as 0.2 T.